Outcomes of vaginal hysterectomy combined with anterior and posterior colporrhaphy for pelvic organ prolapse: a single center retrospective study - Ju Hee Kim; So Young Lee; Hee Dong Chae; Yoon Kyung Shin; Sa Ra Lee; Sung Hoon Kim (Korean Society of Obstetrics and Gynecology, 2022)
Objective To evaluate the efficacy of vaginal hysterectomy combined with anterior and posterior colporrhaphy (VH APR) for the management of pelvic organ prolapse (POP). Methods A total of 610 patients with POP who underwent VH APR from January 2010 to June 2019 at Asan Medical Center were included in this study. We analyzed the patient characteristics and surgical outcomes. In addition, we compared the POP quantification system (POP-Q) pre- and postoperatively at 2 weeks, 3 months, and 1 year, and analyzed the risk factors for recurrence. Results The mean age of the patients was 65.5±7.6 years. The most common preoperative POP-Q stage was stage 2 (60.8%), followed by stage 3 (35.9%). Complications were identified during surgery in 1.6% of the patients. The most common postoperative complication (6.4%) was voiding difficulty. All POP-Q scores significantly decreased at 1 year after surgery (P<0.0001). The recurrence rate was 9.6%, and most recurrences (77.5%) occurred in the anterior compartment. An advanced stage of preoperative POP was a risk factor for recurrence (stage 3 or 4 vs. stage 1 or 2; odds ratio [OR], 5.337, 95% confidence interval [CI], 2.58-11.036, P<0.0001). Only two patients underwent surgical correction for POP recurrence, and most of the remaining patients did not undergo further treatment for prolapse. Conclusion VH APR is a safe and effective surgical procedure for POP, with a low recurrence rate. In addition, advanced preoperative stage was the only risk factor for recurrent POP.